Keterampilan Berbahasa Arab dalam Literatur Akademik Indonesia: Tren Penelitian dalam Jurnal Terakreditasi SINTA (2018-2022) - Hidayat, Ahmad Fadhel Syakir; Nukman, Nukman; Sofian, Ganjar Yusup; Annisa, Maryam Nur (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
Research trends are an important indicator in evaluating the extent to which a field of science has developed, especially in Arabic language skills. It is necessary to know the extent to which previous researchers have studied these skills with various types of methods, approaches, models, instruments, and how much similar research has been carried out. Therefore, this study aims to investigate research trends in Arabic language skills in Indonesian academic literature, with a focus on articles published in accredited journals of SINTA (Science and Technology Index) during the 2018-2022 period. The research method used is SLR (Systematic Literature Review), which is used as a framework for identifying, collecting and reviewing literature. Data will be collected from SINTA accredited journals which contain articles about Arabic language skills totaling 62 journals with 377 articles. This research uses descriptive bibliometric analysis to identify research trends, dominant topics, and Indonesia's contribution to Arabic language skills academic literature. This research has revealed that a lot of research on Arabic language skills carried out in 2021, which is dominant with research on speaking skill, while the type of research used is dominated by quantitative experiments and qualitative case studies, with instruments of interview, observations, questionnaires, tests and documentation being many choices for researchers with descriptive qualitative analysis as well as descriptive statistical analysis. Most research locus are found at junior high school, high school and university levels, while research topics are more directed towards a particular method in Arabic language skills.